2019
DOI: 10.1016/j.neo.2019.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Loss of 1p36.33 Frequent in Low-Grade Serous Ovarian Cancer

Abstract: BACKGROUND: Low-grade serous ovarian cancer (LGSOC) is a rare subtype of epithelial ovarian carcinoma. Limited data regarding the molecular-genetic background exist beyond mutations in the RAS signaling pathway. There is a growing need to better characterize these tumors due to chemoresistance and limited therapeutic options in advanced or recurrent disease. METHODS: We performed genome-wide copy number aberration (CNA) profiles and mutation hotspot screening ( KRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 41 publications
1
33
1
Order By: Relevance
“…Our findings at diagnosis where M2 TAMs are increased at metastatic sites is in line with previous literature data showing that M2 increase the invasiveness of ovarian cancer [24] and that TAM behavior, number, and composition differ according to the tumor area (demonstrated in different solid tumors, but not yet in ovarian cancer [25]). Although often treated similarly, low-grade tumors respond differently to chemotherapy compared to high-grade tumors [26], differ genetically [27], and have a different immune biology. The group of Yang et al demonstrated, based on the retrospective analysis of micro-array datasets, that the gene signature of immune cells is nearly opposite in high-grade serous ovarian cancer compared to low-grade serous ovarian cancer [28].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings at diagnosis where M2 TAMs are increased at metastatic sites is in line with previous literature data showing that M2 increase the invasiveness of ovarian cancer [24] and that TAM behavior, number, and composition differ according to the tumor area (demonstrated in different solid tumors, but not yet in ovarian cancer [25]). Although often treated similarly, low-grade tumors respond differently to chemotherapy compared to high-grade tumors [26], differ genetically [27], and have a different immune biology. The group of Yang et al demonstrated, based on the retrospective analysis of micro-array datasets, that the gene signature of immune cells is nearly opposite in high-grade serous ovarian cancer compared to low-grade serous ovarian cancer [28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LGSOC has a more indolent course than HGSOC, resulting in a longer overall survival (OS). However, LGSOC is more resistant to chemotherapy and has less than 5% response rate to first-line chemotherapy compared to the 80% response rate of HGSOC [ 32 , 33 ].…”
Section: Low Grade Serous Carcinomamentioning
confidence: 99%
“…The most commonly mutated genes are KRAS and BRAF , with these mutations being mutually exclusive [ 25 , 34 , 35 ]. Singer et al., in 2003, reported the first analysis of KRAS and BRAF mutations in LGSOC [ 36 ], and since then, many studies have confirmed the presence of these mutations in LGSOC [ 33 , [37] , [38] , [39] ]. The frequency of mutations ranged from 0% to 32% (mean 7.8%) for BRAF and 15.4%–54.5% (mean 24.2%) for KRAS mutations.…”
Section: Low Grade Serous Carcinomamentioning
confidence: 99%
“…Notably, TP53 R234H mutations were observed in two MEKi-resistant cell lines (CL-07 and CL-08) both with VAF above 96% indicating their clonal origin (Fig 1A, Supplementary Figure 1). While mutations in TP53 are rare in LGSOC tumors (8% frequency) [9,43], these cell lines (which were derived from two sequential tumor samples corresponding to the same patient) had been confirmed to be LGSOC by pathology review [44]. Furthermore, 3% of tumors in the GENIE cohort had TP53 mutations.…”
Section: -4)mentioning
confidence: 99%
“…However, in the last 5-10 years investigators have elucidated many key genomic aberrations, leading to major advancements in the molecular characterization and classification of LGSOC [3,4]. In contrast to other ovarian cancer subtypes, LGSOC are genetically characterized by high frequency of oncogenic mutations in KRAS, NRAS, and BRAF (20-40%, 7-26%, 5-33%, respectively) [5-7], a very low prevalence of TP53 mutations (<8%) [8,9], frequent copy-number deletion of CDKN2A resulting in loss of tumor suppressor protein p16 (15-53%) [10,11], and high expression of estrogen receptor (ER) and progesterone receptor (PR) (>90% and >50%, respectively) [12][13][14]. More recently, less frequent mutations in USP9X (15%) and EIF1AX (8%) have been described in a small proportion of LGSOC tumors [10,15].Traditionally, the therapeutic management of different ovarian cancer histotypes has been similar as it is now appreciated that different ovarian histological subtypes represent different diseases [16].Consequently, the most common treatment for LGSOC is based on cytoreductive surgery followed by platinum/paclitaxel chemotherapy.…”
mentioning
confidence: 99%